Forbidden words: Taboo and the censoring of language - Allan, Keith (Cambridge University, 2013)
Many words and expressions are viewed as 'taboo', such as those used to describe sex, our bodies and their functions, and those used to insult other people. This book provides a fascinating insight into taboo language and its role in everyday life. It looks at the ways we use language to be polite or impolite, politically correct or offensive, depending on whether we are 'sweet-talking', 'straight-talking' or being deliberately rude. Using a range of colourful examples, it shows how we use language playfully and figuratively in order to swear, to insult, and also to be politically correct, and what our motivations are for doing so. It goes on to examine the differences between institutionalized censorship and the ways individuals censor their own language. Lively and revealing, Forbidden Words will fascinate anyone who is interested in how and why we use and avoid taboos in daily conversation.